Stable Isotope Analysis of Two Filter-Feeding Sharks in the Northwestern Pacific Ocean - Chi-Ju Yu; Shoou-Jeng Joung; Hua-Hsun Hsu; Kwang-Ming Liu; Atsuko Yamaguchi (Fishes)
Understanding the feeding ecology and habitat use of vulnerable shark species is crucial for effective conservation. This study focuses on two large filter-feeding sharks, the megamouth shark (Megachasma pelagios) and whale shark (Rhincodon typus), in Northwestern Pacific waters. Stable isotope analysis (δ13C and δ15N) was conducted on white muscle samples (n = 91) of M. pelagios and fin clips (n = 90) of R. typus, collected via large-mesh drift nets and set nets in Taiwanese waters. In this study, we investigated feeding strategies, ontogenetic dietary shifts, habitat use, and isotopic niche variation in both species. For R. typus, the observed positive correlation between δ13C and δ15N supports the previously proposed active suction filter feeding, as well as implying both a diet with an increasing proportion of higher trophic level prey and an ontogenetic shift. In contrast, M. pelagios displayed a negative correlation, consistent with a previous study associating such patterns with primary or secondary consumers, further aligning with its reported planktonic prey dominance. Both species had increasing δ13C with growth, signifying a shift to nutrient-rich habitats. Only R. typus exhibited ontogenetic diet changes (δ15N). SIBER (Stable Isotope Bayesian Ellipses in R) analysis revealed distinct feeding strategies and habitat use between the two species, potential sexual segregation, and wider isotopic niche widths for males in both species. The findings underscore the importance of considering species-specific behaviors and sex-based differences in conservation strategies.